New and Improved Nanomaterials and Approaches for Optical Bio- and Immunosensors - Dzantiev, Boris B. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint presents new approaches for bio- and immunosensors with nanodispersed labels and their optical registration. The use of nanoparticles as carriers and labels provides possibilities for simple measurements and reaching low detection limits. In this way, novel sensors obtain competitive advantages and good potential for implementation into diagnostic practice. The collected articles demonstrate the current state of developments and their most promising directions in the creation and characterization of such optical sensors.